A healing ionomer crosslinked by a bis-bidentate halogen bond linker: a route to hard and healable coatings. Issue 16 (6th April 2018) - Dahlke, J.; Tepper, R.; Geitner, R.; Zechel, S.; Vitz, J.; Kampes, R.; Popp, J.; Hager, M. D.; Schubert, U. S.
Abstract : A bis-bidentate halogen bond linker was introduced into a fully organic, phosphate based ionomer, yielding a crosslinked network with healing abilities and improved mechanical properties. Abstract : In this work we present the first incorporation of bis-bidentate halogen bond linkers into an organic healing ionomer system resulting in the formation of crosslinked supramolecular networks. The obtained supramolecular coatings feature an excellent healing ability as well as an enhanced mechanical performance.